An evaluation of coverage and compliance of mass drug administration 2006 for elimination of lymphatic filariasis in endemic areas of Gujarat - Kumar Pradeep; Prajapati P; Saxena Deepak; Kavishwar Abhay; Kurian George (Wolters Kluwer Medknow Publications, 2008)
Background: Mass drug administration (MDA) means once-in-a-year administration of diethyl carbamazine (DEC) tablet to all people (excluding children under 2 years, pregnant women and severely ill persons) in identified endemic areas. It aims at cessation of transmission of lymphatic filariasis. Objective: What has been the coverage and compliance of MDA in Gujarat during the campaign in December 2006? Study Design: Cross-sectional population based house-to-house visit. Setting: Urban and rural areas in Gujarat identified as endemic for filariasis where MDA 2006 was undertaken. Study Variables: Exploratory - Rural and urban districts; Outcome - coverage, compliance, actual coverage, side effects. Analysis: Percentage and proportions. Results: Twenty-six clusters, each comprising 32 households from six endemic districts, yielded an eligible population of 4164. The coverage rate was 85.2% with variation across different areas. The compliance with drug ingestion was 89% with a gap of 11% to be targeted by intensive IEC. The effective coverage (75.8%) was much below the target (85%). Side effects of DEC were minimum, transient and drug-specific. Overall coverage was marginally better in rural areas. The causes of poor coverage and compliance have been discussed and relevant suggestions have been made.